(3ehUd GdWdGH Edi bhGYO GdEYQGHs - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s; (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa, CHh eMeO, LeGd GdOjf, GHf gTGe ,J (B761 (3g` s ((3GdYQHj Hf CMeO Hf eMeO Hf YHOGdeDef GdOGhOj GdTQja s)
(3ChdgG (B:s
(3hHYO, agPG TQM dWja Ydi bhGYO GdEYQGH, SCdfjg HYV GdCUMGH, jMd GdeHGfj s
(3BNQgG (B:s
(3adPdc MV Ydi GdJCed aj NJe GdcJGH ceG aYd aj GaJJGMg bGd(B: (3JbJVj HeJCedgG LGOI GdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3HgG CKQ WeSs
(3TQM dcJGH bhGYO GdGYQGH Gh GdGYQGH Yf bhGYO GdGYQGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs